INTEREST IN FOREIGN LANGUAGE LEARNING - Halim Shanty (Institut Agama Islam Negeri Palopo, 2019)
This article describes about the interest in foreign language learning. Interest is a state of wanting to learn or know about curiosity. Interest has a mayor effect towards the learning activity. Interest is a permanent inclination to pay and recall several activities (Djamarah, 2008:48). Interest has a major effect towards the learning activity. Interest is feeling and commitment to something or activity without command. Interest is often regard as being a major element in the teacher’s store of motivational tactics (McDonouch, 2013:143). Interest is acceptation to one connection between one self and outside more and more close the connection bigger interest (Slameto, 2008:180). There are six factors that influence learning interest, namely: motivation, attention, attitude, study habit, self concept and student aptitude